Polymethyl methacrylate and ionic liquid blended thermoplastic composite material as well as preparation method and application thereof
By blending polymethyl methacrylate with specific ionic liquids, the brittleness problem of thermoplastic polymer materials at room temperature and the volatility problem of plasticizers is solved, and the mechanical properties and transparency of the material are improved, suitable for a variety of purposes Engineering applications.
Patent Information
- Application Number
- CN202310778884.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
Thermoplastic polymer materials such as polymethyl methacrylate are brittle materials at room temperature, limiting their engineering applications, and the volatility of plasticizers in commercially available products leads to a decrease in mechanical properties.
Polymethyl methacrylate is blended with a specific ionic liquid, which is freely dispersed around the polymer backbone, acting as a plasticizer to regulate its glass transition temperature and mechanical properties.
It significantly reduces the glass transition temperature of polymethyl methacrylate, improves its elongation of break and tensile strength, enhances transparency and mechanical properties, and is suitable for applications in different scenarios.
Smart Images

Figure CN119220039A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a thermoplastic composite material of polymethyl methacrylate and ionic liquid blended therein and a preparation method and application thereof, belonging to the field of composite materials. Background Art
[0002] Thermoplastic polymers have the advantages of high strength, low cost and reprocessability. However, most thermoplastic polymers are brittle polymers at room temperature, which limits their wider application. Therefore, it is very important to achieve toughening of thermoplastic polymers for their engineering applications. Polymethyl methacrylate, as a commonly used thermoplastic plastic, is widely used in the optical field because of its excellent optical properties. However, polymethyl methacrylate exhibits brittle fracture at room temperature, with an elongation at break of about 5%, which greatly limits its application in engineering. Commercially available polymethyl methacrylate products usually contain phthalate plasticizers. Phthalate plasticizers have certain volatility at high temperatures, which will cause the mechanical properties of polymethyl methacrylate to decrease. Summary of the invention
[0003] To solve the above problems, the present invention provides the following technical solutions:
[0004] A thermoplastic composite material is obtained by blending a polymer and an ionic liquid, wherein the polymer is polymethyl methacrylate.
[0005] According to an embodiment of the present invention, the ionic liquid is freely dispersed around the polymer main chain without changing the structure of the polymer main chain.
[0006] According to an embodiment of the present invention, the raw materials of the thermoplastic composite material include at least:
[0007] Polymethyl methacrylate 100 parts by mass
[0008] 10 to 100 parts by mass of ionic liquid.
[0009] According to an embodiment of the present invention, the ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt, 1-hexyl-3-methylimidazolium hexafluorophosphate and 1-butyl-3-methylimidazolium trifluoromethanesulfonate.
[0010] According to an embodiment of the present invention, the glass transition temperature of the ionic liquid is -50°C to -100°C, for example, -80°C.
[0011] According to an embodiment of the present invention, the structural formula of the polymethyl methacrylate is as shown in formula (1):
[0012]
[0013] Here, n is selected from 1000 to 100000, for example, 1000, 5000, 10000, 50000, and 100000.
[0014] According to an embodiment of the present invention, the weight average molecular weight of the polymethyl methacrylate is preferably 200,000-1,500,000, for example, 200,000, 300,000, 500,000, 800,000, or 1,000,000.
[0015] According to an embodiment of the present invention, in the raw material, the ionic liquid is 20 parts by mass, 30 parts by mass, 40 parts by mass, 50 parts by mass, 60 parts by mass, 70 parts by mass, 80 parts by mass, or 90 parts by mass.
[0016] According to an embodiment of the present invention, in the raw material, the mass ratio of polymethyl methacrylate to ionic liquid is 100:(10-100), for example, 100:20, 100:30, 100:40, 100:50, 100:60, 100:70, 100:80, 100:90.
[0017] According to an embodiment of the present invention, the imidazolium cation in the ionic liquid and the ester group of polymethyl methacrylate interact with each other through hydrogen bonds, the ionic liquid is freely dispersed around the polymer main chain, and the two can achieve mutual compatibility in any proportion, for example, the mass ratio of polymethyl methacrylate to ionic liquid is 100:(10~100).
[0018] According to an embodiment of the present invention, compared with polymethyl methacrylate, the glass transition temperature of the thermoplastic composite material is reduced by 1 to 100° C., for example, 10 to 100° C.
[0019] According to an embodiment of the present invention, the glass transition temperature of the thermoplastic composite material is 10-110°C, for example, 106.5°C, 103.8°C, 98.5°C, 76.3°C, 70.3°C, 67.2°C, 35.7°C, 24.5°C, or 19.6°C.
[0020] According to an embodiment of the present invention, the thermoplastic composite material has good mechanical properties.
[0021] According to an embodiment of the present invention, the tensile strength of the thermoplastic composite material is 1-50 MPa, for example, 2 MPa, 10 MPa, 20 MPa, 30 MPa, 40 MPa, or 48.97 MPa.
[0022] According to an embodiment of the present invention, the elongation at break of the thermoplastic composite material is 1%-650%, for example, 4%, 5%, 10%, 50%, 100%, 200%, 300%, 400%, 500%, 600%.
[0023] According to the embodiment of the present invention, the thermoplastic composite material has good transparency, and the transparency can reach more than 90%, for example, 90.5%, 91.0%, 91.5%.
[0024] The present invention also provides a method for preparing the above-mentioned thermoplastic composite material, which comprises: dissolving the above-mentioned raw materials by a co-solvent, mixing them uniformly, and then volatilizing the co-solvent to achieve blending and prepare the thermoplastic composite material.
[0025] According to an embodiment of the present invention, the raw material has the meaning as described above.
[0026] According to an embodiment of the present invention, the co-solvent may be selected from at least one of dichloromethane, tetrahydrofuran, and chloroform, for example, dichloromethane or tetrahydrofuran.
[0027] According to an embodiment of the present invention, the dissolution may be performed by methods known in the art, for example, at least one of the following methods:
[0028] Method 1: dissolving polymethyl methacrylate and ionic liquid in a co-solvent respectively and mixing them evenly;
[0029] Method 2: first dissolve polymethyl methacrylate in a co-solvent, then add the ionic liquid to dissolve, and mix well;
[0030] Method three: first dissolve the ionic liquid in the co-solvent, then add polymethyl methacrylate to dissolve, and mix well.
[0031] According to an embodiment of the present invention, the co-solvent can be used in an amount known in the art, as long as the raw material can be dissolved. For example, the amount of the co-solvent is 10-10000 parts by mass, for example, 1000 parts by mass, per 100 parts by mass of polymethyl methacrylate.
[0032] According to an embodiment of the present invention, the mixing conditions during dissolution may be selected from those known in the art, such as a mixing temperature of 25°C.
[0033] According to an embodiment of the present invention, mixing is stopped when the solution becomes clear and transparent.
[0034] According to an embodiment of the present invention, the volatilization conditions of the co-solvent may be selected from conditions known in the art, such as a volatilization temperature of 25°C.
[0035] The present invention also provides an application of the thermoplastic composite material, which can be used in the field of processing and forming, such as molding, calendering, extrusion, injection, etc. In the present invention, the thermoplastic composite material can be used in the field of processing and forming by thermoplastic plastic processing technology known in the art.
[0036] Beneficial effects:
[0037] The glass transition temperature of polymethyl methacrylate is about 110-130°C, and it is in a glassy state at room temperature, so its fracture is brittle fracture. The glass transition temperature of the ionic liquid selected in the present invention is about -80°C, and it is compatible with polymethyl methacrylate, so the ionic liquid plays the role of a plasticizer.
[0038] Compared with existing thermoplastic composite materials, the glass transition temperature of the thermoplastic composite material of the present invention is effectively reduced, and the blended thermoplastic composite material has good compatibility, high transparency, strong toughness, and easily adjustable mechanical properties.
[0039] The present invention obtains a thermoplastic composite material with different mechanical properties by blending polymethyl methacrylate with an ionic liquid, and the mechanical properties of the thermoplastic composite material range from elastomers to tough plastics. Test results show that:
[0040] 1. The blended thermoplastic composite material has excellent mechanical properties, with a tensile strength of up to 48MPa and an elongation at break of up to 620%, which can meet the application needs in different scenarios.
[0041] 2. The blended thermoplastic composite material has the characteristic of being easy to adjust. By adjusting the mass ratio of polymethyl methacrylate and ionic liquid, the elongation at break and tensile strength of the mechanical material can be conveniently adjusted. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the molecular structure of polymethyl methacrylate and three imidazole-type ionic liquids.
[0043] Figure 2 The dumbbell-shaped spline appearance of the blended thermoplastic composite material prepared by film pressing corresponds to Examples 1-9 from left to right.
[0044] Figure 3 Room temperature stress-strain curves of the blended thermoplastic composite materials prepared in Examples 1-3.
[0045] Figure 4 Room temperature stress-strain curves of the blended thermoplastic composite materials prepared in Examples 4-6.
[0046] Figure 5Room temperature stress-strain curves of the blended thermoplastic composite materials prepared in Examples 7-9. DETAILED DESCRIPTION
[0047] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0048] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0049] Example 1
[0050] Preparation of a blended thermoplastic composite material: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 1000000) and 10 mass parts of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt are successively dissolved in dichloromethane and mixed evenly, the amount of dichloromethane used is 1000 mass parts, and the mixing condition is 25°C; when the solution is clear and transparent, the mixing is stopped, and then the dichloromethane is evaporated cleanly, the volatilization condition is 25°C, and a polymethyl methacrylate and ionic liquid blended thermoplastic composite material is obtained.
[0051] Performance Test:
[0052] The test method is as follows: the blended thermoplastic composite material of this embodiment is molded to obtain a dumbbell-shaped specimen with a length of 35 mm and a thickness of 1.5 mm. The dumbbell-shaped specimen is then subjected to a mechanical test on an Instron universal tensile machine at a tensile rate of 20 mm / min and a temperature of 25°C.
[0053] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 48.97 MPa and an elongation at break of 4.75%.
[0054] Example 2
[0055] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 500000) and 10 mass parts of 1-hexyl-3-methylimidazole hexafluorophosphate are dissolved in tetrahydrofuran and mixed evenly, the amount of tetrahydrofuran is 1000 mass parts, and the mixing condition is 25° C. When the solution is clear and transparent, the mixing is stopped, and then the tetrahydrofuran is evaporated to obtain a thermoplastic composite material blended with polymethyl methacrylate and ionic liquid.
[0056] Performance Test:
[0057] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0058] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 41.02 MPa and an elongation at break of 4.02%.
[0059] Example 3
[0060] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 800000) and 10 mass parts of 1-butyl-3-methylimidazole trifluoromethanesulfonate are successively dissolved in dichloromethane and mixed evenly, the amount of dichloromethane used is 1000 mass parts, and the mixing condition is 25° C.; when the solution is clear and transparent, the mixing is stopped, and then the dichloromethane is evaporated cleanly, and the volatilization condition is 25° C., to obtain a polymethyl methacrylate and ionic liquid blended thermoplastic composite material.
[0061] Performance Test:
[0062] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0063] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 41.27 MPa and an elongation at break of 5.14%.
[0064] Example 4
[0065] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 1000000) and 40 mass parts of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt are successively dissolved in dichloromethane and mixed evenly, the amount of dichloromethane used is 1000 mass parts, and the mixing condition is 25° C.; when the solution is clear and transparent, the mixing is stopped, and then the dichloromethane is evaporated cleanly, and the volatilization condition is 25° C., to obtain a polymethyl methacrylate and ionic liquid blended thermoplastic composite material.
[0066] Performance Test:
[0067] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0068] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 34.96 MPa and an elongation at break of 21.20%.
[0069] Example 5
[0070] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 500000) and 40 mass parts of 1-hexyl-3-methylimidazole hexafluorophosphate are dissolved in tetrahydrofuran and mixed evenly, the amount of tetrahydrofuran is 1000 mass parts, and the mixing condition is 25° C. When the solution is clear and transparent, the mixing is stopped, and then the tetrahydrofuran is evaporated cleanly, and the volatilization condition is 25° C., to obtain a thermoplastic composite material blended with polymethyl methacrylate and ionic liquid.
[0071] Performance Test:
[0072] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0073] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 32.04 MPa and an elongation at break of 42.22%.
[0074] Example 6
[0075] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 800000) and 40 mass parts of 1-butyl-3-methylimidazole trifluoromethanesulfonate are successively dissolved in dichloromethane and mixed evenly, the amount of dichloromethane used is 1000 mass parts, and the mixing condition is 25° C.; when the solution is clear and transparent, the mixing is stopped, and then the dichloromethane is evaporated cleanly, and the volatilization condition is 25° C., to obtain a polymethyl methacrylate and ionic liquid blended thermoplastic composite material.
[0076] Performance Test:
[0077] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0078] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 18.56 MPa and an elongation at break of 235.60%.
[0079] Example 7
[0080] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 1000000) and 100 mass parts of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt are dissolved in dichloromethane and mixed evenly, the amount of dichloromethane used is 1000 mass parts, and the mixing condition is 25° C.; when the solution is clear and transparent, the mixing is stopped, and then the dichloromethane is evaporated cleanly, and the volatilization condition is 25° C., to obtain a polymethyl methacrylate and ionic liquid blended thermoplastic composite material.
[0081] Performance Test:
[0082] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0083] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 2.71 MPa and an elongation at break of 624.85%.
[0084] Example 8
[0085] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 500000) and 100 mass parts of 1-hexyl-3-methylimidazole hexafluorophosphate are dissolved in tetrahydrofuran and mixed evenly, the amount of tetrahydrofuran used is 1000 mass parts, and the mixing condition is 25° C.; when the solution is clear and transparent, the mixing is stopped, and then the tetrahydrofuran is evaporated cleanly, and the volatilization condition is 25° C., to obtain a thermoplastic composite material blended with polymethyl methacrylate and ionic liquid.
[0086] Performance Test:
[0087] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0088] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 2.32 MPa and an elongation at break of 446.23%.
[0089] Example 9
[0090] The steps for preparing the blended thermoplastic composite material in this embodiment are the same as those in Example 1, except that: based on the mass parts of polymethyl methacrylate, 100 mass parts of polymethyl methacrylate (weight average molecular weight: 800000) and 100 mass parts of 1-butyl-3-methylimidazole trifluoromethanesulfonate are dissolved in dichloromethane and mixed evenly, the amount of dichloromethane used is 1000 mass parts, and the mixing condition is 25° C.; when the solution is clear and transparent, the mixing is stopped, and then the dichloromethane is evaporated cleanly, and the volatilization condition is 25° C., to obtain a polymethyl methacrylate and ionic liquid blended thermoplastic composite material.
[0091] Performance Test:
[0092] The testing method of this embodiment is the same as that of embodiment 1, except that the blended thermoplastic composite material of this embodiment is molded to obtain dumbbell-shaped specimens with a length of 35 mm and a thickness of 1.5 mm, and then a mechanical test is performed.
[0093] Tests show that the blended thermoplastic composite material of this embodiment has excellent mechanical properties, with a tensile strength of 7.46 MPa and an elongation at break of 382.19%.
[0094] Test Example 1
[0095] The thermoplastic composite materials of Examples 1-9 were taken to test their glass transition temperatures. The test was performed using a TA Q200 DSC instrument. 5 mg of the sample was placed in an aluminum crucible and put into the instrument for testing. The test was divided into three heating and cooling cycle processes. The first process was from 40°C to 180°C, the second process was from 180°C to -100°C, and the third process was from -100°C to 180°C. The glass transition temperature was determined in the third process, and the heating and cooling rate was 10°C / min. The transmittance was tested using an ultraviolet-visible spectrometer UV 2600. The sample was pressed to obtain a film with a thickness of 0.5 mm. The transmittance in the 400-760nm band was tested and the average value was recorded in Table 1.
[0096] Table 1 Properties of thermoplastic composites
[0097] sample Glass transition temperature Transmittance Example 1 103.8℃ 91.5% Example 2 70.3℃ 90.3% Example 3 24.5℃ 90.8% Example 4 106.5℃ 91.3% Example 5 76.3℃ 90.4% Example 6 35.7℃ 91.0% Example 7 98.5℃ 91.3% Example 8 67.2℃ 90.6% Example 9 19.6℃ 91.1%
[0098] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A thermoplastic composite material, characterized in that: The thermoplastic composite material is obtained by blending a polymer and an ionic liquid, wherein the polymer is polymethyl methacrylate; The ionic liquid is freely dispersed around the polymer main chain without changing the structure of the polymer main chain.
2. The thermoplastic composite material according to claim 1, characterized in that Calculated per 100 parts by mass of polymethyl methacrylate, the raw materials of the thermoplastic composite material at least include: Polymethyl methacrylate 100 parts by mass 10 to 100 parts by mass of ionic liquid.
3. The thermoplastic composite material according to claim 1 or 2, characterized in that: The ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt, 1-hexyl-3-methylimidazolium hexafluorophosphate and 1-butyl-3-methylimidazolium trifluoromethanesulfonate. Preferably, the glass transition temperature of the ionic liquid is -50°C to -100°C.
4. The thermoplastic composite material according to any one of claims 1 to 3, characterized in that: The structural formula of the polymethyl methacrylate is shown in formula (1): Wherein, n is selected from 1000 to 100000. Preferably, the weight average molecular weight of the polymethyl methacrylate is preferably 200,000-1,500,000.
5. The thermoplastic composite material according to any one of claims 1 to 4, characterized in that: In the raw materials, the mass ratio of polymethyl methacrylate to ionic liquid is 100:(10-100).
6. The thermoplastic composite material according to any one of claims 1 to 5, characterized in that: Compared with polymethyl methacrylate, the glass transition temperature of the thermoplastic composite material is reduced by 1-100°C. Preferably, the glass transition temperature of the thermoplastic composite material is 10-110°C.
7. The thermoplastic composite material according to any one of claims 1 to 6, characterized in that: The tensile strength of the thermoplastic composite material is 1-50 MPa. Preferably, the elongation at break of the thermoplastic composite material is 1%-650%. Preferably, the transparency of the thermoplastic composite material is above 90%.
8. The method for preparing the thermoplastic composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: dissolving the above raw materials by a co-solvent, mixing them uniformly, and then volatilizing the co-solvent to achieve blending and prepare the thermoplastic composite material.
9. The preparation method according to claim 8, characterized in that: The co-solvent is selected from at least one of dichloromethane, tetrahydrofuran and chloroform. Preferably, the amount of the co-solvent used is 10-10000 parts by mass per 100 parts by mass of polymethyl methacrylate.
10. Use of the thermoplastic composite material according to any one of claims 1 to 7.
